2010
DOI: 10.4322/rbpv.01902012
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Leishmania spp. em felinos do município de AraÇatuba, SP

Abstract: This study had the purpose to compare the occurrence of Leishmania spp. in felines through two methods (cytological and serological), as well as to associate the occurrence of this protozoan with the sex, age and breed variables. Serum samples from 283 domestic felines were processed by means of Indirect Immunofluorescence Reaction (IIR), and the direct parasitological test for linfonodes was also carried out in order to verify positivity for Leishmania spp. Occurrence of 0.7% (2/283) was observed in the teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 15 publications
(8 reference statements)
1
9
2
2
Order By: Relevance
“…Costa et al (2010) observed 11.5% positivity using ELISA. However, the prevalence found in this study was higher than those reported by Bresciani et al (2010) and Silveira (2010), which both used ELISA and obtained 3.5% positivity. Figueiredo et al (2009) also found lower values in a study focusing on Rio de Janeiro; they reported 2.4% positivity using ELISA.…”
Section: Discussioncontrasting
confidence: 55%
“…Costa et al (2010) observed 11.5% positivity using ELISA. However, the prevalence found in this study was higher than those reported by Bresciani et al (2010) and Silveira (2010), which both used ELISA and obtained 3.5% positivity. Figueiredo et al (2009) also found lower values in a study focusing on Rio de Janeiro; they reported 2.4% positivity using ELISA.…”
Section: Discussioncontrasting
confidence: 55%
“…This study revealed the occurrence of L. infantum antibodies in 6.6% of the sampled cats, which is higher than that found in previous studies conducted in another areas endemic for leishmaniasis in the state of São Paulo, Brazil, where seroprevalence ranging from 0.5 to 4.64% has been reported, using the same serological technique (IFAT) and cut-off (≥ 40) (SOBRINHO et al, 2012;CARDIA et al, 2013;BRESCIANI et al, 2010). On the other hand, Vides et al (2011) reported a higher seroprevalence by IFAT (10.9%) among cats sampled in the city of Araçatuba, state of São Paulo, which was higher than that found in this study, probably because all the cats sampled in the former study showed dermatologic lesions, one of the most suggestive clinical signs of feline leishmaniasis (SOLANO-GALLEGO et al, 2007).…”
Section: Discussioncontrasting
confidence: 45%
“…Lower seropositivity to Leishmania spp. among cats compared to dogs in areas endemic for leishmaniasis have been reported in previous studies (SOLANO-GALLEGO et al, 2007;BRESCIANI et al, 2010;SOBRINHO et al, 2012;CARDIA et al, 2013). According to Solano-Gallego et al (2007), the immune response in cats, mainly cellular immunity, is effective enough to control the infection and confer some natural resistance (GARCIA et al, 1999)., Differences in specificity and sensitivity among different techniques used in earlier studies are likely the cause of disparate seroprevalence rates.…”
Section: Discussionmentioning
confidence: 89%
“…Although IFAT has been used in epidemiological studies (Ayllon et al 2008;Poli et al 2002;Vita et al 2005), the positive animals of the present study were not seroreactive by IFAT but by ELISA, results similar to that obtained by Figueiredo et al (2009), who evaluated antibodies anti-Leishmania in 43 cats from Barra Mansa Municipality, Rio de Janeiro State, Brazil by the methods IFAT and ELISA and detected only one reactive animal, 2.4% (1/43), by the latter technique only. Bresciani et al (2010) found 0.7% (2/283) of cats positive for Leishmania spp. by the IFAT technique in the municipality of Araçatuba, São Paulo State, Brazil.…”
Section: Discussionmentioning
confidence: 98%